2018
DOI: 10.2196/10203
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Learning for Children in Pediatric Care: Qualitative Study Assessing Educational Challenges

Abstract: Learning is seen as an active construction process and the individual´s life world is the basis for the individual´s understanding, thinking and action [1, 2]. Learning is a meaning making construction process about new or modified interpretations of perceptions and experiences and involves the whole person. Meaning, knowledge and understanding are created based on different kinds of information, data and by and in interaction with people, artifacts and the environment [2, 3]. No one can passively

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(35 citation statements)
references
References 53 publications
0
35
0
Order By: Relevance
“…The actual interactive website was to a high extent used by the confident children in this study. In another study, the interactive website was analysed based on a pedagogical framework (Lööf, Andersson‐Papadogiannakis, Karlgren, & Silén, ). The analysis showed that an interactive website offer possibilities for children to learn by building on their own curiosity and interest, identification with others experiences and by getting answers related to their concerns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The actual interactive website was to a high extent used by the confident children in this study. In another study, the interactive website was analysed based on a pedagogical framework (Lööf, Andersson‐Papadogiannakis, Karlgren, & Silén, ). The analysis showed that an interactive website offer possibilities for children to learn by building on their own curiosity and interest, identification with others experiences and by getting answers related to their concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Even though children are prepared for the expected procedures, they most likely will be exposed to new, unexpected experiences highlighting the importance of not restricting children's need of information and preparation to a single event. A continuous process signified by individualized adjustments and flexibility recognizing that children need to process the information received to fully understand and be prepared has to be provided (Lööf et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The aim is to describe common themes characterizing the object being studied. The directed content analysis approach in this study builds on a previous investigation [ 18 ] that provided a theoretical basis of children’s learning on a website. This approach is judged to be appropriate since the analysis is operationalized based on previous knowledge that would benefit from further refinement or development.…”
Section: Methodsmentioning
confidence: 99%
“…Learning is a multifaceted phenomenon that requires processing of information cognitively, emotionally, and socially through testing and practical actions [ 21 , 22 ]. The learning concepts of preunderstanding, motivation, learning processes, and learning outcomes, which were previously used in a theoretical analysis of a Web-based preparation program for children [ 18 ], are used in this study to analyze and describe children’s approach to a website consisting of a comprehensive, interactive, age-differentiated multimedia Web-based portal aimed to prepare and educate children and their families before pediatric perioperative care (see Multimedia Appendix 1 for further explanation of central learning concepts).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation